Micro-vascular surgery in fingertip injury treatment: Case report - Rosadi Seswandhana Teddy OH Prasetyono Chaula Sukasah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
A high priority for fingertip injury reconstruction is the restoration of skin cover to protect underlying bone, tendon,and nerve structures. Other priorities are to maintain or maximize sensibility, preserve digit length, and minimizecosmetic deformity. Because it is so highly visible, though, the appearance of the reconstructed digit should be asnormal as possible. Therefore, microvascular surgery has an important role in management of fingertip injuries togive a normal shape of the digit. In this case, a clinical experience using microvascular surgery in the treatment offingertip injury was reported. In early 2007, there were two fingertip injury cases which were reconstructed usingmicrovascular surgery modality. The first case was a 34 years old male who had defect in soft tissue of the fourthfinger in his right hand caused by pressed machine. We performed elective wound reconstruction by transferring theskin and soft tissue freely (free pulp transfer) along with the vasculatures taken from fibular side of great toe in theright foot. Revascularization was performed by connecting deep plantar artery/vein with common digital artery/veinat the injured digit. The second case, was a 29 years old female with clean-cut amputation of the distal part of thethird finger in the right hand (Allen’s type IV). We performed replantation in the first 16 hours after injury. Wereanastomosed the ulnar side of digital artery only without vein and nerve reanastomosis. To avoid the distal edema,we did not perform any skin suture and let the oozing from the vein backflow. In both cases, we have excellentappearance result, moderate usefulness of the finger, but still poor in sensibility.Key words: clinical experiences - fingertip injury - soft tissue defect - clean cut amputation - microvascular surgery- free pulp transfer - replantation.